Effect of irrigation methods, nitrogen and calcium spray on physical and chemical characteristics of watermelon “Top yield” var. (Citrullus lanatus) in Sulaimani Governorate - Malmood, Ayub Karim; Omar, Samal Jalal (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was carried out at Kanipanka Research Station / Sulaymani during growing season of 2015 to study the effect of irrigation method, nitrogen and calcium spraying and their interaction on chemical and physical characteristics of watermelon plant ("Top yield" var.).The study included surface and drip irrigation spraying nitrogen as three concentrations (0, 200 and 400 mg N l-1) using urea fertilizer and spraying calcium (0, 100, 300, 600 mg Ca l-1) concentrations using CaCl2. The experiment was conducted as factorial experimental (2 x 3 with (3) replication. The study's characters were some physical and chemical characters. The results showed that surface (furrow) irrigation was significant in dry matter % (4.17 %) and Ca (0.92 %). N2 (400 mg l-1) was significant in dry matter (4.36 %) and N (0.18%) . While Ca3 (600 ml l-1) was superior in dry matter (4.95 %), Ca (1.21 %), fruit size (3.73 L) and rind thickness (0.92 cm). The interactions of irrigation methods, nitrogen and calcium were significantly affected on some characters. (S x N2 x Ca3) was superior in dry matter% (5.26 %), sucrose % (3.510 %), pH value (5.90) and rind thickness (1.06 cm).
Keywords: Water melon; Irrigation method; Calcium; Nitrogen; Physical and Chemical propertie